Developing a partially perfused liver model using caprine liver explant conditioned to the chicken extra-embryonic perfusion system. (February 2020) - Swaminathan, Akila; Ranganathan, Srinithi; Baskar, Kala; Bhuvaneswari, Srinivasan; Skandaprasad, Sivasri; Gajalakshmi, Palanivel; Chatterjee, Suvro
Highlights: Development of the combination of avian extra-embryonic perfusion system with the explanted liver tissue. This model was increased the life span of the liver explants tissue. This model was increased the liver functions in the fibrotic stress induced explants tissue. This model was attenuated the collagen synthesis in the anti- fibrotic drug treated explants tissue. Abstract: The Liver is constantly subjected to mechanical, chemical and pathological insults throughout life, as a result of which there is a common occurrence of various liver diseases. Due to the complex nature of liver architecture, it is not possible to mimic the in-vivo conditions beyond a certain limit. Hence, the development of in-vitro and ex-vivo models to study various liver diseases has gained more importance over the last few decades. The present study aims to develop a semi-perfused liver explant model to give an extended lifetime for studying liver pathology and treatment options. Caprine liver tissue explants were sliced, weighed (25 mg) and placed on the area vasculosa of fertilized chicken eggs. Unfertilized eggs were used as controls. After varying time intervals of incubation on area vasculosa of fertilized chicken eggs, the liver slices were subjected to cell viability assay, lactate dehydrogenase assay and Serum glutamic pyruvic transaminase assays. The results indicate that the viability and functional properties of such semi-perfused liver tissue explants holds good up to 6 h. Finally, the liver tissue explants were pre-treated with FBS, with and without anti-fibrotic drugs, and placed on chick embryo area vasculosa up to 6 h. The anti-fibrotic drug-treated semi perfused liver tissue explant showed a decrease in collagen formation as confirmed by histology and western blot. We deem that the use of extra-embryonic vasculature of chicken bed for extending the life of tissue explants will serve as a cost-effective alternative to animal models to understand disease mechanisms under drug treatments.